French consumer evaluation of eating quality of Angus x Salers beef: Effects of muscle cut, muscle slicing and ageing. (March 2023) - Liu, Jingjing; Pannier, Liselotte; Ellies-Oury, Marie-Pierre; Legrand, Isabelle; Noel, Faustine; Sepchat, Bernard; Prache, Sophie; Pethick, David; Hocquette, Jean-François
Abstract: Based on the Meat Standards Australia (MSA) methodology, the objectives of this study were to evaluate the eating quality of grass-fed Angus x Salers beef by French consumers, across different muscle cuts ( m. triceps brachii caput longum, m. longissimus dorsi et thoracis and m. rectus abdominis ), ageing times (5 and 14 days) and muscle slicing and grilling methods (being distinguished by 2 different sides on the grill), and to further quantify whether the MSA model could predict the eating quality of the meat produced by these lean crossbred animals. The results showed that French consumers can discern significant differences in eating quality traits across muscle cuts but not between ageing times and muscle slicing methods. In this study, the accuracy of eating quality score (MQ4)-assigned MSA grade was 64.5%. Due to the lack of MSA data on these lean crossbred animals, the prediction of eating quality from carcass characteristics was less accurate than usual. However, these results do indicate that the MSA sensory testing protocol, the MQ4 calculation and the MSA quality grades could be used to support a consumer-based quality grading system in France. Highlights: The MSA grading scheme and prediction model are relevant for French consumer evaluation of grass-fed Angus x Salers beef. French consumers can discern differences in eating quality traits of different cuts from grass-fed Angus x Salers animals. It is relevant to develop a consumer-based grading system for beef eating quality prediction in France.